Cervical cancer incidence in elderly women-biology or screening history?. (March 2017) - Lynge, Elsebeth; Lönnberg, Stefan; Törnberg, Sven
Abstract: Aim: In many countries, the age-specific pattern of cervical cancer incidence is currently bipolar with peaks at for instance 45 and 65 years of age. Consequently, a large proportion of cervical cancer cases are presently diagnosed in women above the screening age. The purpose of the study was to determine whether this bipolar pattern in age-specific incidence of cervical cancer reflects underlying biology or can be explained by the fact that the data come from birth cohorts with different screening histories. Methods: Combination of historical data on cervical screening and population-based cancer incidence data from Denmark 1943–2013, Finland and Norway 1953–2013, and Sweden 1958–2013. Results: Since the implementation of screening, the incidence of cervical cancer has decreased for each successive birth cohort. All birth cohorts showed a unipolar age-specific pattern. In unscreened women in Denmark and Sweden, the incidence peaked around the age of 50; the peak was less marked in Finland; while peak age for unscreened women could not be determined for Norway due to widespread opportunistic screening. The current old-age peak in the incidence of cervical cancer represents residuals from unscreened or underscreened birth cohorts. Conclusion: The current bipolar pattern in age-specific incidence of cervical cancer can largely be explained by the different screening histories of successive birth cohorts. While it is reasonable to offer screening to elderly women today, birth cohort trends in disease burden should be carefully monitored to justify permanent changes in upper screening age. Highlights: Peak in cervix cancer in elderly women attributed to new partners or HPV reactivation. No peak in elderly women in Nordic cervix cancer data for successive birth cohorts. Present bipolar pattern reflects screening history rather than biology. Screening policy for elderly women should take birth cohort trends into account.